Using word square and scramble methods to improve residential thematic learning outcomes in class IV students of SD negeri 104205 Tembung - Ahmad Landong; Hidayat; Rindi Pransiska; Dhea Ramadhani; Amanda Putri Ayuni (Institute of Computer Science (IOCS), 2023)
This study described the increase in learning outcomes in the environment subject around me using the healthy square and scramble learning method for fourth grade students at SD Negeri 104205 Tembung. This two-period group study collected data through tests and observations. The study found that fourth graders at SD Negeri 104205 Tembung learned more about residential areas using quadratic and mixed methods. The study found that fourth graders at SD Negeri 104205 Tembung learned more about residential areas using quadratic and mixed methods. Cycle I's post-test results showed 15 students (42%) with perfect scores and 63 20 students (58%). In cycle II, 33 students (95%) had very good achievement and 2 (5%) had an average total achievement of 85. In addition, the results of observing learning implementation in cycle I averaged 77% (good) and cycle II increased to 92% (very good), and student activity in cycle I averaged 62 (enough) and cycle II increased to 93 (very good). The first cycle averaged 62 and the second 93. Thus, the researcher's word square and scramble learning methods improved my district's students' learning outcomes.